Microbes on the “peachy spots” of ancient Kaihua paper: microbial community and functional analysis - Zhou, Yanjun; Shi, Yan; Huang, Yanyan; Zhong, Jiang (Frontiers in Microbiology, 2024)
Kaihua paper is a type of precious hand-made paper in China that has been used throughout Chinese history. Due to its extraordinary whiteness and fine texture, it was adopted by the imperial palace in the reign of Emperor Kang Xi and Yong Zheng of the Qing Dynasty of China in the 17th and 18th century. It is stained by a special type of yellowish-brown spot after years of storage, which is called a “peachy spot”. The formation of such spots remains unclear, although complicated physicochemical processes or microbial activities might be involved. We performed nondestructive sampling and high-throughput sequencing to determine the bacterial and fungal communities on peachy spot surfaces. By comparing the unstained areas and air samples in the stack room, we found that peachy spot formation was mainly related to bacterial communities rather than fungal communities. Significantly more potential acid-producing, acidophilic or cellulase-producing bacteria, such as Lactobacillus, Streptococcus, Staphylococcus, and Lysinibacillus, and pigment-producing bacteria, such as Methylobacterium and Rubrobacter, were identified in the peachy spot samples. Prediction of the functional genes of the bacterial community also suggested the production of acidic substance pigments. These findings provide new insights into the pigment formation mechanism in ancient paper and open an opportunity to develop new strategies to preserve the ancient paper documents.